Self-constitution agency, identity, and integrity - Korsgaard, Christine M. (Christine Marion) (Oxford : Oxford University Press, 2009)
Christine M. Korsgaard presents an account of the foundation of practical reason and moral obligation, based on a new theory of action and interaction. She proposes that the function of an action is to constitute the agency and therefore the identity of the person who does it, and that only morally good action can serve this function.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Practical reason; Agent (Philosophy); Responsibility